Multicentre evaluation of non-invasive biatrial mapping for persistent atrial fibrillation ablation: the AFACART study. Issue 8 (15th February 2017) - Knecht, Sébastien; Sohal, Manav; Deisenhofer, Isabelle; Albenque, Jean-Paul; Arentz, Thomas; Neumann, Thomas; Cauchemez, Bruno; Duytschaever, Mattias; Ramoul, Khaled; Verbeet, Thierry; Thorsten, Sonia; Jadidi, Amir; et al.
Abstract: Aims: Non-invasive electrocardiogram (ECG) mapping allows the activation of the entire atrial epicardium to be recorded simultaneously, potentially identifying mechanisms critical for atrial fibrillation (AF) persistence. We sought to evaluate the utility of ECG mapping as a practical tool prior to ablation of persistent AF (PsAF) in centres with no practical experience of the system. Methods and results: A total of 118 patients with continuous AF duration <1 year were prospectively studied at 8 European centres. Patients were on a median of 1 antiarrhythmic drug (AAD) that had failed to restore sinus rhythm. Electrocardiogram mapping (ECVUE™, CardioInsight, USA) was performed prior to ablation to map AF drivers (local re-entrant circuits or focal breakthroughs). Ablation targeted drivers depicted by the system, followed by pulmonary vein (PV) isolation, and finally left atrial linear ablation if AF persisted. The primary endpoint was AF termination. Totally, 4.9 ± 1.0 driver sites were mapped per patient with a cumulative mapping time of 16 ± 2 s. Of these, 53% of drivers were located in the left atrium, 27% in the right atrium, and 20% in the anterior interatrial groove. Driver-only ablation resulted in AF termination in 75 of the 118 patients (64%) with a mean radiofrequency (RF) duration of 46 ± 28 min. Acute termination rates were not significantly different amongst all 8 centres ( P = 0.672). Ten additional patients terminated with PV isolation and lines resulting in a total AF termination rate of 72%. Total RF duration was 75 ± 27 min. At 1-year follow-up, 78% of the patients were off AADs and 77% of the patients were free from AF recurrence. Of the patients with no AF recurrence, 49% experienced at least one episode of atrial tachycardia (AT) which required either continued AAD therapy, cardioversion, or repeat ablation. Conclusion: Non-invasive mapping identifies biatrial drivers that are critical in PsAF. This is validated by successful AF termination in the majority of patients treated in centres with no experience of the system. Ablation targeting these drivers results in favourable AF-free survival at 1 year, albeit with a significant rate of AT recurrence requiring further management.